2019
DOI: 10.1016/j.jnutbio.2019.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics mixture increases butyrate, and subsequently rescues the nigral dopaminergic neurons from MPTP and rotenone-induced neurotoxicity

Abstract: Please cite this article as: S. Srivastav, S. Neupane, S. Bhurtel, et al., Probiotics mixture increases butyrate, and subsequently rescues the nigral dopaminergic neurons from MPTP and rotenone-induced neurotoxicity, The Journal of Nutritional Biochemistry, https://doi. AbstractMicrobiota in the gut affect brain physiology via various pathways, and dysbiosis seems to play a role in the pathogenesis of Parkinson's disease (PD). Probiotics showed pleiotropic effects on functions of the central nervous system via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
142
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(154 citation statements)
references
References 52 publications
12
142
0
Order By: Relevance
“…Similar neuroprotective effects have also been reported using oral administration of probiotics or fecal microbiota transplantation from normal mice in PD animal models [27,67,68]. The role of probiotics in ameliorating dopaminergic neuronal loss could be attributed to their actions of inhibiting glial cell activation and neuroinflammation, increasing butyrate level, and elevating the level of some neurotrophic factors such as brain-derived neurotrophic factor (BDNF) or glial cell line-derived neurotrophic factor (GDNF) [27,67,68]. Earlier studies have reported that the administration of probiotics increased the levels of BDNF and GDNF, which are required for the survival of dopaminergic neurons in vivo [67,69].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Similar neuroprotective effects have also been reported using oral administration of probiotics or fecal microbiota transplantation from normal mice in PD animal models [27,67,68]. The role of probiotics in ameliorating dopaminergic neuronal loss could be attributed to their actions of inhibiting glial cell activation and neuroinflammation, increasing butyrate level, and elevating the level of some neurotrophic factors such as brain-derived neurotrophic factor (BDNF) or glial cell line-derived neurotrophic factor (GDNF) [27,67,68]. Earlier studies have reported that the administration of probiotics increased the levels of BDNF and GDNF, which are required for the survival of dopaminergic neurons in vivo [67,69].…”
Section: Discussionsupporting
confidence: 71%
“…The present study, based on the animal behavioral and histological results, indicates that the early (starting at 8 weeks of age) and long-term (16 weeks) probiotic intervention may induce the preservation of several comprehensive motor functions through the protection of the nigrostriatal dopamine neurons. Similar neuroprotective effects have also been reported using oral administration of probiotics or fecal microbiota transplantation from normal mice in PD animal models [27,67,68]. The role of probiotics in ameliorating dopaminergic neuronal loss could be attributed to their actions of inhibiting glial cell activation and neuroinflammation, increasing butyrate level, and elevating the level of some neurotrophic factors such as brain-derived neurotrophic factor (BDNF) or glial cell line-derived neurotrophic factor (GDNF) [27,67,68].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Possibility because of butyrate can induce the BDNF and glial cell line-derived neurotrophic factor (GDNF) upregulated, and monoamine-oxidase was inhibited in the brain. Furthermore, probiotics mixture pretreatment can reduce DA neurons loss, increase the level of DA and reduce the activity of inflammatory cells of brain (Srivastav et al, 2019).…”
Section: Probioticsmentioning
confidence: 99%
“…Butyrate is under a wide range of biological functions. Studies have shown that butyrate plays an active role in brain disorders in a variety of neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease, and Huntington's disease [9][10][11][12]. Sodium butyrate (NaB) is a common form of butyrate.…”
Section: Introductionmentioning
confidence: 99%